Perancangan Sign System Kawasan Outbound Edukasi Satwa, Agro & Perikanan di Alas Outbound Prambon - Tirta Adi Nugraha; Sri Wulandari (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Alas Outbound is an educational tourist destination in Simpang village, Prambon District, Sidoarjo regency, which offers various facilities and activities, such as playground rides, swimming pools, fish ponds, mud ponds, and education about animals, plantations, Fisheries, and natural scenery. The Merdeka Campus Competition Program (PKKM) of the Visual Communication Design Education Program of the National Development University "Veteran" East Java was held here with the aim of designing a sign system design and a floor plan for the educational outbound area. Its remote location makes it difficult for the community to find it, so it needs environmental graphics in the form of a sign system that includes area plans, location instructions, and information about various areas on the educational outbound pedestal. The design of this sign system is divided into three phases: pre-production, production, and post-production. The graphics used in this sign system are taken from the theme of several areas in Alas Outbound education that focuses on the advantages of Agro Education. There are three main types of sign systems, including 14 animal education information sign designs, 6 plantation education information sign designs, 1 fisheries education information sign Design, 2 welcome signs that highlight animal education & agro education, and 1 map sign. Although each type of sign system has uniformity in the form of boards and text colors, gate signs have differences in the form of plates and text colors to be easily distinguished by visitors. All signs are placed around the educational animal and Agro educational educational outbound Alas Prambon, Sidoarjo, in accordance with the type and purpose of each to provide clear guidance to visitors about the location, information, and areas that they can visit in the educational outbound Alas.